2013
DOI: 10.1073/pnas.1316316110
|View full text |Cite
|
Sign up to set email alerts
|

Tudor domain containing 12 (TDRD12) is essential for secondary PIWI interacting RNA biogenesis in mice

Abstract: Significance Large parts of eukaryotic genomes are composed of transposons. Mammalian genomes use DNA methylation to silence these genomic parasites. A class of small RNAs called Piwi-interacting RNAs (piRNAs) is used to specifically guide the DNA methylation machinery to the transposon DNA elements. How germ cells make piRNAs is not entirely understood. We identify a mouse protein and demonstrate its importance for transposon silencing. We find that the protein collaborates with other factors alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 37 publications
(49 reference statements)
0
92
0
Order By: Relevance
“…TDRD5 (also called meiosis arrest female 1, MARF1) is essential for oogenesis and the development of healthy offspring 32. TDRD proteins were demonstrated to be essential for male mice fertility including Tdrd1,33 Tdrd12,34 Tdrkh35 and Tdrd5 36. Only recently was a TDRD1 polymorphic variant in the 5’-UTR of exon 1 reported to associate with spermatogenic failure susceptibility in a dominant model in the Han Chines 37.…”
Section: Discussionmentioning
confidence: 99%
“…TDRD5 (also called meiosis arrest female 1, MARF1) is essential for oogenesis and the development of healthy offspring 32. TDRD proteins were demonstrated to be essential for male mice fertility including Tdrd1,33 Tdrd12,34 Tdrkh35 and Tdrd5 36. Only recently was a TDRD1 polymorphic variant in the 5’-UTR of exon 1 reported to associate with spermatogenic failure susceptibility in a dominant model in the Han Chines 37.…”
Section: Discussionmentioning
confidence: 99%
“…The ping-pong amplification mechanism is particularly predominant in fetal male germ cells that are challenged by the global resetting of the male germline epigenome, which causes an induction of the transposon expression. To initiate the amplification cycle in mice, MILI associates with primary piRNAs and operates in the ping-pong cycle together with other factors to yield antisense secondary piRNAs that in turn associate with MIWI2 (De Fazio et al 2011, Pandey et al 2013, Yang et al 2015. MIWI2 then translocates to the nucleus where it initiates transcriptional transposon silencing via DNA methylation at the target loci (Aravin et al 2008, Kuramochi-Miyagawa et al 2008, De Fazio et al 2011.…”
Section: Germ Granules As Platforms For Pirna Pathwaymentioning
confidence: 99%
“…However, the exact functional mechanism of Piwi/ piRNA complexes remains unclear. Based on the findings of all reviewed studies, piRNA biogenesis-associated genes have been shown to be vital for spermatogenesis [32].…”
Section: Discussionmentioning
confidence: 99%